Analysis of Remuneration System Satisfaction and Its Affecting Factors (Case Study on Specialist-Physician at Government Hospital in Jakarta) - Pratiwi, Citra Sari; Meliala, Andreasta (Rumah Sakit Akademik Universitas Gadjah Mada, 2023)
Background: Remuneration is an important strategy to improve the competence of hospital services. Remuneration aims to motivate employees which can be achieved if the remuneration system is implemented fairly, but the gap between the ratio of the number of doctors and the average points to rates causes’ physician dissatisfaction toward the remuneration system. Analyze satisfaction level and measure remuneration satisfaction factors on Pediatricians and Obstetrics and Gynecologists at ABC Hospital Jakarta. Methods:This study used quantitative methods with multiple linear regression analysis measured by the Equity Scale and Remuneration Satisfaction Scale. Interviews were used to obtain comprehensive analysis results from respondents who were in the lower and upper limits of the questionnaire results. The interview also involved the management of ABC Hospital Jakarta.Results:Total 44 respondents consisting of 30 Pediatricians and 14 Obstetricians and Gynecologists, showed dissatisfaction with the remuneration system (45,46%), neutral (31,53%), and satisfied (23%). There was a relationship between perceptions of external fairness (P= 0,003) and procedural fairness (P= 0,002) with remuneration satisfaction. There was no relationship between perceptions of internal justice (P= 0,929) and perceptions of individual justice (P= 0,130) with remuneration satisfaction. These results were explored using interviews and the causes of doctor dissatisfaction due to the gap in the achievement of the Individual Performance Index, lots of doctor examinations that were not listed in the rates, and remuneration points did not consider the complexity of each job. Meanwhile, the dissatisfaction felt by the management was due to the lack of measurement of quality indicators in the remuneration system.Conclusion: External and procedural justices are factors that affect the satisfaction of remuneration felt by specialist-physician. The remuneration obtained at ABC Hospital Jakarta is lower than other Government Hospitals of the same type. In addition, there are binding rules, doctors' lack of understanding of the remuneration system, and lack of socialization. The management needs to formulate a more detailed remuneration system based on applicable regulations by adjusting the hospital situation.